2013
DOI: 10.1007/s10533-013-9843-3
|View full text |Cite
|
Sign up to set email alerts
|

Strong gradient of benthic biogeochemical processes along a macrotidal temperate estuary: focus on P and Si cycles

Abstract: International audienceThis study aims to investigate the role of spatial and temporal physical, biological and biogeochemical gradients on sediment biogeochemistry along a macrotidal and Si-rich estuary. Scanning and biogeochemical analyses were performed in the inner, mid and outer Aulne Estuary (France) at four seasons. The inner estuary shows high diagenetic activity linked to fluid mud dynamics and river loads. The highest authigenic phosphorus (Aut-P) concentrations ever found in the literature are observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 78 publications
(104 reference statements)
1
13
2
Order By: Relevance
“…et al, 2013;Raimonet et al, 2013). In the present study, the observed DSi concentration of the upper estuaries are similar to those reported earlier for Indian rivers Gurumurthy et al, 2012;Meunier et al, 2015;Frings et al, 2015) and other tropical rivers (Liu et al, 2009;Hughes et al, 2011Hughes et al, , 2012Ran et al, 2015).…”
Section: Comparison With Previous Si Data In Riverssupporting
confidence: 92%
See 1 more Smart Citation
“…et al, 2013;Raimonet et al, 2013). In the present study, the observed DSi concentration of the upper estuaries are similar to those reported earlier for Indian rivers Gurumurthy et al, 2012;Meunier et al, 2015;Frings et al, 2015) and other tropical rivers (Liu et al, 2009;Hughes et al, 2011Hughes et al, , 2012Ran et al, 2015).…”
Section: Comparison With Previous Si Data In Riverssupporting
confidence: 92%
“…It is known that ASi dissolution at the sediment -water interface can be a significant supply of DSi in estuaries Delvaux et al, 2013;Raimonet et al, 2013). Our data do not allow quantifying such benthic flux, but we suggest that it should contribute significantly to the high DSi concentration in this cluster.…”
Section: Inter-estuary Biogeochemical Processesmentioning
confidence: 65%
“…The transformation, preservation, and recycling of P at the sediment-water interface are largely controlled by the reactivity of different forms of P (Ruttenberg, 1992;Slomp et al, 1996a;Mort et al, 2010), and driven by a number of biological, physical and geochemical processes (Schenau and De Lange, 2001;Slomp et al, 2013). Numerous studies have shown that estuarine and coastal areas are important P sinks and function as P filters (Fang et al, 2007;Raimonet et al, 2013;Bonaglia et al, 2014) due to their fairly high sedimentation rate and phosphorus burial efficiency. However, sediments can also provide a significant source of P for the water column (Lewandowski et al, 2003;Krom et al, 2010;Zaaboub et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, some other processes such as Auth-Ca-P formation could counterbalance the decrease in dissolved Fe/P and N/P ratios in scavenging dissolved phosphate (Ruttenberg et al 1992;Raimonet et al 2013). The enhanced liberation of pore water HPO 2À 4 arising from Orga-P mineralization or from Fe-P dissolution should promote Auth-Ca-P precipitation (Slomp et al 1996;Raimonet et al 2013).…”
Section: Consequences For the Phosphorus Cyclementioning
confidence: 99%
“…The enhanced liberation of pore water HPO 2À 4 arising from Orga-P mineralization or from Fe-P dissolution should promote Auth-Ca-P precipitation (Slomp et al 1996;Raimonet et al 2013). In the Aber Benoît, Auth-Ca-P precipitation and Fe-P precipitation in superficial sediments in May (beneath oysters) and in June and at the end of July in deeper layers (Reference) could partly explain the sharp rise in the ratio between dissolved ammonium and phosphate (NH þ 4 /HPO 2À 4 ) and dissolved iron and phosphate (Fe 2?…”
Section: Consequences For the Phosphorus Cyclementioning
confidence: 99%